Optimism and pessimism in games - Eichberger, Jürgen; Kelsey, David (International economic review, 2014)
This article considers the impact of ambiguity in strategic situations. It extends the existing literature on games with ambiguity-averse players by allowing for optimistic responses to ambiguity. We use the CEU model of ambiguity with a class of capacities introduced by Jaffrray and Philippe (Mathematics of Operations Research 22 (1997), 165-85), which allows us to distinguish ambiguity from ambiguity-attitude, and propose a new solution concept, equilibrium under ambiguity (EUA), for players who may be characterized by ambiguity-preference. Applying EUA, we study comparative statics of changes in ambiguity-attitude in games with strategic complements. This extends work in Eichberger and Kelsey (Journal of Economic Theory 106 (2002), 436-66) on the effects of increasing ambiguity if players are ambiguity averse.
Gesehen am 16.09.2020